Evaluation of Round Window Stimulation Performance in Otosclerosis Using Finite Element Modeling. (29th February 2016) - Yang, Shanguo; Xu, Dan; Liu, Xiaole
Abstract : Round window (RW) stimulation is a new type of middle ear implant's application for treating patients with middle ear disease, such as otosclerosis. However, clinical outcomes show a substantial degree of variability. One source of variability is the variation in the material properties of the ear components caused by the disease. To investigate the influence of the otosclerosis on the performance of the RW stimulation, a human ear finite element model including middle ear and cochlea was established based on a set of microcomputerized tomography section images of a human temporal bone. Three characteristic changes of the otosclerosis in the auditory system were simulated in the FE model: stapedial annular ligament stiffness enlargement, stapedial abnormal bone growth, and partial fixation of the malleus. The FE model was verified by comparing the model-predicted results with published experimental measurements. The equivalent sound pressure (ESP) of RW stimulation was calculated via comparing the differential intracochlear pressure produced by the RW stimulation and the normal eardrum sound stimulation. The results show that the increase of stapedial annular ligament and partial fixation of the malleus decreases RW stimulation's ESP prominently at lower frequencies. In contrast, the stapedial abnormal bone growth deteriorates RW stimulation's ESP severely at higher frequencies.